Magnetic nanoparticle containing thiol-ene crosslinked hydrogels for controlled and targeted release of hydrophobic drugs - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN; DEMİR, SERAP (WILEY, 2018)
This study reports a straightforward but very effective method to produce nanocomposite hydrogels for targeted drug delivery system. An organic network containing both hydrophilic and hydrophobic components was obtained using thiol-ene cross-linking. Magnetite nanoparticles (MNPs) were synthesized by chemical co-precipitation. The surface of the MNPs was modified with allyl groups to avoid agglomeration. Composite hydrogels were prepared by addition of surface modified MNPs to hydrogel formulation at different ratios. The prepared composite hydrogels were investigated for their ability to loading and release hydrophobic drugs tamoxifen and clarithromycin. The morphological and structural characterizations of MNPs were performed by Fourier transform infrared spectroscopy (FT-IR) and Environmental scanning electron microscopy (SEM) and Environmental scanning transmission electron microscopy (STEM). Moreover the superparamagnetic behavior of the hydrogels was studied by a vibrating sample magnetometer (VSM). The saturation magnetization values increased with the magnetite content. Swelling, gel content and degradation of the hydrogels were examined. According to the loading of drugs, the maximum loading efficiency was 91% for tamoxifen and 70% for clarithromycin due to the stronger hydrophobic interactions. In vitro release studies showed that controlled release of the drugs occurred over a prolonged period of time. Therefore, drug loaded hydrogels can be considered as potential long-term sustained drug release systems. POLYM. COMPOS., 39:E200-E209, 2018. (c) 2016 Society of Plastics Engineers
Keywords: IRON-OXIDE NANOPARTICLES; BIOMEDICAL APPLICATIONS; DELIVERY SYSTEMS; NANOCOMPOSITE HYDROGELS; HYDROLYTIC DEGRADATION; COPOLYMERS; CHITOSAN; CANCER; FE3O4; BRAIN